Wawasan Al-Qur’an Tentang Kalender Islam (Perkembangan Upaya Penyatuan di Indonesia) - Rupi’i Amri (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2016)
The Moslem people in Indonesia still have different ways to determine the first day of the Islamic calendar. The different decision result in the difference in starting in performing certain religious service, the most preminent thing is in starting to perform fast in Ramadan and in Id Fitr and Id Adha Festival.The difference is due to two cases, that is, in determining the rule and the siystem or the way in determining the first day of the month. This article is intend to know how the concept of the Qur’an about Islamic calendar and the development of the unification of Islamic calendar in Indonesia. The research findings are (1) the dominant concepts of Islamic calendar in Indonesia are the hisab concept of Muhammadiyah about the determining of the first day of the Islamic calendar, i.e. Hisab Hakiki Wujud al-Hilal, and the ru’ya concept of Nahdatul Ulama (NU); (2) The figures who strongly tries to unite the Islamic calendar in Indonesia are Thomas Djamaluddin and Susiknan Azhari. Djamaluddin’s concept on the crescent visibility criteria as an effort to unite Islamic calendar in Indonesia is based on the redefinition of hilal, the aplication rukyah al-hilal or matla’, and hilal visibility criteria (imkan ar-rukyah) in 2000 and 2011; (3) Susiknan Azhari explains that the relationships between Muhammadiyah and NU related by the determining of the first day of Islamic calendar are four models, they are conflict, independent, dialogue, and integration.